Persistence of humoral response upon SARS‐CoV‐2 infection. (30th June 2021) - Knies, Andrea; Ladage, Dennis; Braun, Ralf J.; Kimpel, Janine; Schneider, Miriam
Summary: SARS‐CoV‐2 continues to leave its toll on global health and the economy. Management of the pandemic will rely heavily on the degree of adaptive immunity persistence following natural SARS‐CoV‐2 infection. Along with the progression of the pandemic, more literature on the persistence of the SARS‐CoV‐2‐specific antibody response is becoming available. Here, we summarize findings on the persistence of the humoral, including neutralizing antibody, response at three to eight months post SARS‐CoV‐2 infection in non‐pregnant adults. While the comparability of the literature is limited, findings on the detectability of immunoglobulin G class of antibodies (IgG) were most consistent and were reported in most studies to last for six to eight months. Studies investigating the response of immunoglobins M and A (IgM, IgA) were limited and reported mixed results, in particular, for IgM. The majority of studies observed neutralizing antibodies at all time points tested, which in some studies lasted up to eight months. The presence of neutralizing antibodies has been linked to protection from re‐infection, suggesting long‐term immunity to SARS‐CoV‐2. These neutralizing capacities may be challenged by emerging virus variants, but mucosal antibodies as well as memory B and T cells may optimize future immune responses. Thus, further longitudinal investigation of PCR‐confirmed seropositive individuals using sensitive assays is warranted to elucidate the nature and duration of a more long‐term humoral response.